CURRENT APPROACHES TO THE TREATMENT OF PATIENTS WITH ENDOMETRIAL HYPERPLASIA - Uzokova , M.K.; Boltaeva , G.I. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Objective — To analyze the main aspects of endometrial hyperplasia (EH), including its causes, clinical significance, health risks for women, as well as to review modern treatment approaches, including surgical and medical methods, as well as the prospects of alternative therapeutic methods. Endometrial hyperplasia (EH) represents a set of morphological changes in the uterine mucosa, the primary manifestation of which is the proliferation of glandular epithelium and an increase in the gland-to-stroma ratio. The relevance of this pathology is due to its high prevalence, ranging from 10% to 55%, according to various data. The clinical significance of EH is primarily associated with the potential risk of malignancy and the development of endometrial cancer. The key pathogenic mechanisms contributing to the development of hyperplasia are absolute or relative hyperestrogenism and insufficient progesterone production, which fails to counteract the proliferative effect of estrogens. Women at higher risk include those with early onset of menstruation, late onset of menopause, ovulatory disorders, infertility, polycystic ovary syndrome, as well as those undergoing estrogen monotherapy, tamoxifen treatment, obesity, type 2 diabetes, hypertension, Lynch syndrome, or estrogen-producing ovarian tumors. Leading specialists agree that effective treatment of EH should include surgical intervention, supplemented by medical correction aimed at eliminating risk factors and reducing the likelihood of disease recurrence. Despite numerous clinical studies confirming the effectiveness of various treatment approaches, the issue of applying alternative methods remains a subject of scientific discussion. This highlights the need for further research and optimization of treatment regimens for patients with endometrial hyperplasia. Conclusion: Endometrial hyperplasia (EH) is of great relevance due to its high prevalence and close association with the risk of developing endometrial cancer. Given the increasing number of patients with various risk factors, such as hormonal disorders, obesity, and chronic diseases, it is important to continue researching diagnostic and therapeutic methods for EH. Special attention should be given to the development of optimal treatment regimens, which should not only include standard surgical and medical methods but also evaluate the effectiveness of alternative approaches. This is necessary to improve patients’ quality of life and reduce the risk of disease recurrence, highlighting the importance of further scientific research in this area.